1989
DOI: 10.1128/jb.171.7.3634-3640.1989
|View full text |Cite
|
Sign up to set email alerts
|

Purification and N-terminal sequence of the alpha subunit of antigen 43, a unique protein complex associated with the outer membrane of Escherichia coli

Abstract: Antigen 43 has been identified as a unique protein complex in the outer membrane of Escherichia coli. The complex contains two different polypeptides, a (Mrs 60,000) and ,( (Mrs 53,000), in equal stoichiometry (P. Owen, P. Caffrey, and L.-G. Josefsson, J. Bacteriol. 169:3770-3777, 1987). The a subunit was released in a water-soluble form upon heating of outer membranes to 60°C and was purified to apparent homogeneity by gel filtration and ion-exchange chromatography. The purified protein was acidic (pl 4.6) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
46
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 49 publications
5
46
0
Order By: Relevance
“…This explains why the heat extraction, which is performed at 60°C, results in the release of a mostly unfolded mature protein. In previous studies, the mature forms of AIDA-I or Ag43 were purified from heat extracts by gel filtration rather than the IMAC step that we used (7,29). Presumably, the former procedure can separate correctly folded from denatured protein whereas the latter does not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This explains why the heat extraction, which is performed at 60°C, results in the release of a mostly unfolded mature protein. In previous studies, the mature forms of AIDA-I or Ag43 were purified from heat extracts by gel filtration rather than the IMAC step that we used (7,29). Presumably, the former procedure can separate correctly folded from denatured protein whereas the latter does not.…”
Section: Discussionmentioning
confidence: 99%
“…Like TibA and AIDA-I, Ag43 is glycosylated and mediates adhesion to cultured epithelial cells (49), has a similar 19-amino-acid repeat, and promotes autoaggregation (44). Furthermore, like AIDA-I, Ag43 is cleaved by an unknown mechanism after its outer membrane translocation and is not known to mediate invasion (7).…”
mentioning
confidence: 99%
“…As such, antigen 43 was one of the first autotransporters identified, however, it was not until much later that its mode of biogenesis was uncovered (204). In the intervening period, much time was invested in the biochemical characterization of this protein; Owen and coworkers (54,370) demonstrated that antigen 43 existed as a bipartite complex of two proteins (termed ␣ 43 and ␤ 43 ) which could be resolved under denaturing conditions. These subunit proteins were found to exist in a stoichiometric fashion at a ratio of 1:1, and the interaction between the two proteins was noncovalent.…”
Section: Antigen 43mentioning
confidence: 99%
“…The biological function of Ag43 is controversial. In addition to its phase variability, Ag43 displays several properties common to adhesins, as follows: (i) Ag43 possesses two RGD motifs of the type implicated in binding to human integrins, (ii) like many fimbrial subunits the passenger domain (␣ 43 ) can be released from E. coli outer membranes by brief heating to 60°C, (iii) Ag43 displays sequence homology with several known adhesins, (iv) Ag43 mediates bacterial aggregation, and (v) Ag43 confers a low level of adhesion to certain mammalian cells (18,71,74,115). The levels of adhesion to mammalian cells may not be biologically significant (119), but Ag43-mediated autoaggregation apparently contributes to biofilm formation and may enhance colonization of the mammalian intestine.…”
Section: Nonprotease Autotransporters Of Enterobacteriaceaementioning
confidence: 99%